Characterising the metabolic functionality of the preterm neonatal gut microbiome prior to the onset of necrotising enterocolitis: a pilot study - Jonathan A. Chapman; Emily Wroot; Toby Brown; Lauren C. Beck; Nicholas D. Embleton; Janet E. Berrington; Christopher J. Stewart (BMC Microbiology)
Abstract Background Necrotising enterocolitis (NEC) is a devastating bowel disease that primarily occurs in infants born prematurely and is associated with abnormal gut microbiome development. While gut microbiome compositions associated with NEC have been well studied, there is a lack of experimental work investigating microbiota functions and their associations with disease onset. The aim of this pilot study was to characterise the metabolic functionality of the preterm gut microbiome prior to the onset of NEC compared with healthy controls. Results Eight NEC infants were selected of median gestation 26.5 weeks and median day of life (DOL) of NEC onset 20, with one sample used per infant, collected within one to eight days (median four) before NEC onset. Each NEC case was matched to a control infant based on gestation and sample DOL, the main driver of microbiome composition in this population, giving a total cohort of 16 infants for this study. Dietary exposures were well matched. The microbiota of NEC and control infants showed similar wide-ranging metabolic functionalities. All 94 carbon sources were utilised to varying extents but NEC and control samples clustered separately by supervised ordination based on carbon source utilisation profiles. For a subset of eight samples (four NEC, four control) for which pre-existing metagenome data was available, microbiome composition was found to correlate significantly with metabolic activity measured on Biolog plates (p = 0.035). Comparisons across all 16 samples showed the NEC microbiota to have greater utilisation of carbon sources that are the products of proteolytic fermentation, specifically amino acids. In pairwise comparisons, L-methionine was highly utilised in NEC samples, but poorly utilised in controls (p = 0.043). Carbon sources identified as discriminatory for NEC also showed a greater enrichment for established markers of inflammatory disease, such as inflammatory bowel disease, irritable bowel syndrome and diverticular disease. Conclusions Before NEC onset, the preterm gut microbiota showed greater metabolic utilisation of amino acids, potentially indicating a shift from predominantly saccharolytic to proteolytic fermentation. Products of amino acid breakdown could therefore act as biomarkers for NEC development. A larger study is warranted, ideally with infants from multiple sites.